Human lung fibroblast-derived matrix facilitates vascular morphogenesis in 3D environment and enhances skin wound healing. (May 2017) - Du, Ping; Suhaeri, Muhammad; Ha, Sang Su; Oh, Seung Ja; Kim, Sang-Heon; Park, Kwideok
Graphical abstract: Abstract: Extracellular matrix (ECM) is crucial to many aspects of vascular morphogenesis and maintenance of vasculature function. Currently the recapitulation of angiogenic ECM microenvironment is still challenging, due mainly to its diverse components and complex organization. Here we investigate the angiogenic potential of human lung fibroblast-derived matrix (hFDM) in creating a three-dimensional (3D) vascular construct. hFDM was obtained via decellularization of in vitro cultured human lung fibroblasts and analyzed via immunofluorescence staining and ELISA, which detect multiple ECM macromolecules and angiogenic growth factors (GFs). Human umbilical vein endothelial cells (HUVECs) morphology was more elongated and better proliferative on hFDM than on gelatin-coated substrate. To prepare 3D construct, hFDM is collected, quantitatively analyzed, and incorporated in collagen hydrogel (Col) with HUVECs. Capillary-like structure (CLS) formation at 7 day was significantly better with the groups containing higher doses of hFDM compared to the Col group (control). Moreover, the group (Col/hFDM/GFs) with both hFDM and angiogenic GFs (VEGF, bFGF, SDF-1) showed the synergistic activity on CLS formation and found much larger capillary lumen diameters with time. Further analysis of hFDM via angiogenesis antibody array kit reveals abundant biochemical cues, such as angiogenesis-related cytokines, GFs, and proteolytic enzymes. Significantly up-regulated expression of VE-cadherin and ECM-specific integrin subunits was also noticed in Col/hFDM/GFs. In addition, transplantation of Col/hFMD/GFs with HUVECs in skin wound model presents more effective re-epithelialization, many regenerated hair follicles, better transplanted cells viability, and advanced neovascularization. We believe that current system is a very promising platform for 3D vasculature construction in vitro and for cell delivery toward therapeutic applications in vivo . Statement of Significance: Functional 3D vasculature construction in vitro is still challenging due to the difficulty of recapitulating the complex angiogenic extracellular matrix (ECM) environment. Herein, we present a simple and practical method to create an angiogenic 3D environment via incorporation of human lung fibroblast-derived matrix (hFDM) into collagen hydrogel. We found that hFDM offers a significantly improved angiogenic microenvironment for HUVECs on 2D substrates and in 3D construct. A synergistic effect of hFDM and angiogenic growth factors has been well confirmed in 3D condition. The prevascularized 3D collagen constructs also facilitate skin wound healing. We believe that current system should be a convenient and powerful platform in engineering 3D vasculature in vitro, and in delivering cells for therapeutic purposes in vivo .